Metal-Free Conjugate Addition of Alkenylboronic Acids to Enedicarbonyl Compounds towards the Synthesis of Pyridazine Derivatives - Roscales, Silvia; Sancho, Ainhoa; Csákÿ, Aurelio G. (Synthesis, 2015)
The regioselective conjugate addition of alkenylboronic acids to electronically-differentiated 1,4-enedicarbonyl compounds under metal-free conditions, using tartaric acid as promoter of the reaction is reported. The resulting compounds have been used as starting materials in the synthesis of 4-alkenyl-4,5-dihydropyridazin-3(2H)-ones or 4-alkylpyridazin-3(2H)-ones by reaction with hydrazine hydrate and acetic acid.
Keywords: boron; cyclization; isomerization; Michael addition; nucleophilic addition